A novel Fer/FerT targeting compound selectively evokes metabolic stress and necrotic death in malignant cells. Issue 1 (December 2017) - Elkis, Yoav; Cohen, Moshe; Yaffe, Etai; Satmary-Tusk, Shirly; Feldman, Tal; Hikri, Elad; Nyska, Abraham; Feiglin, Ariel; Ofran, Yanay; Shpungin, Sally; Nir, Uri
Abstract Disruption of the reprogrammed energy management system of malignant cells is a prioritized goal of targeted cancer therapy. Two regulators of this system are the Fer kinase, and its cancer cell specific variant, FerT, both residing in subcellular compartments including the mitochondrial electron transport chain. Here, we show that a newly developed inhibitor of Fer and FerT, E260, selectively evokes metabolic stress in cancer cells by imposing mitochondrial dysfunction and deformation, and onset of energy-consuming autophagy which decreases the cellular ATP level. Notably, Fer was also found to associate with PARP-1 and E260 disrupted this association thereby leading to PARP-1 activation. The cooperative intervention with these metabolic pathways leads to energy crisis and necrotic death in malignant, but not in normal human cells, and to the suppression of tumors growth in vivo. Thus, E260 is a new anti-cancer agent which imposes metabolic stress and cellular death in cancer cells. The tyrosine-kinases Fer/FerT associate with the mitochondrial electron transport chain in cancer cells supporting their metabolic reprogramming. Here the authors discover a compound that disrupts Fer /FerT activity and selectively induces cell death of cancer cell lines displaying anti-tumor activity in vivo.